La aesthesis trans-moderna en la zona fronteriza eurasiática y el anti-sublime decolonial - Tlostanova, Madina (CALLE14: revista de investigación en el campo del arte, 2011)
The article considers transmodern aesthesis in relation to the agenda of liberating the aesthetic sphere from the myths of Western modernity. The author offers a critical survey of the main contemporary Western aesthetic trends vis-à-vis the decolonial anti-sublime as an alternative model analyzed in the article. Specific attention is paid to the mechanism of this sublime, grounded in a pluritopic hermeneutic and a decolonial “community of sense” uniting those who were marked by the “colonial wound”. The article focuses on the decolonial reformulating of usual aesthetic issues, such as the correlation of beauty and aesthesis, the relation of knowledge and art, the moral sphere and aesthetics, etc. Finally, a large part is devoted to decolonial aesthesis of theEurasian borderlands: the territories in the East (Central Asia) and South (Caucasus) of the Eurasian continent which used to be Russian/Soviet colonies and have produced complex instances of decolonial art in the works of Saule Suleymenova, Zorikto Dorzhiev and others.